Divo Ti Vyin? Where Are You From? Red River Métis Knowledge as Pedagogy - Garand, Arielle T. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
This article explores the integration of Red River Métis cultural identity into pedagogy, emphasizing the benefits for diverse students in the Canadian context. Using personal narratives and historical connections, it highlights the implications of land-based learning and critical historical analysis to infuse Indigenous perspectives into the elementary educational environment. The article investigates the historical and cultural roots of the Red River Métis, the impact of colonialism on their identity, and the role of Métis matriarchy in cultural continuity. Including Métis histories in the classroom is used to advocate for relational, land-based, and community-oriented pedagogies that honour Indigenous knowledge and promote reconciliatory education. The article also discusses the role of land acknowledgements and community-based events in creating inclusive connections to Indigenous epistemologies. By incorporating Métis pedagogies, educators can create inclusive, collaborative, and reflective learning experiences that support all students in understanding complex historical issues pertinent to their local geography and the broader Canadian society.